2022
DOI: 10.1155/2022/6737248
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Natural Bioactive Ursolic Acid in Embryonic Cancer Stem Cells

Abstract: Embryonic cancer cells (CSCs) could cause different types of cancer, a skill that makes them even more dangerous than other cancer cells. Identifying CSCs using natural products is a good option as it inhibits the recurrence of cancer with moderate various effects. Ursolic acid (UA) is a pentacyclic triterpenoid extracted from fruit and herbal remedies and has known anticancer functions against various cancer cells. However, its potential against CSCs remains uncertain. This study was planned to examine the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…To enlighten the molecular mechanisms of the cytotoxicity of UA ( Figure 1 A) on cancer cells, we first examined its ability to kill various types of cancer cells in culture by detecting plasma membrane-permeabilized cells using a membrane-impermeable propidium iodide (PI) dye. In agreement with previous reports [ 7 , 9 , 47 , 48 ], treatment with UA for 24 h induced death in human breast adenocarcinoma (MCF7) cells, osteosarcoma (U2OS) cells, cervical adenocarcinoma (HeLa) cells, and colorectal carcinoma (HCT116) cells in a dose-dependent manner, with lethal dose 50 (LD 50 ) values of 12.8 µM, 7.7 µM, 16.8 µM, and 19 µM, respectively ( Figure 1 B; Supplementary Figure S1B ). Even at a concentration of 8 μM that only killed ~5.5% of MCF7 cells in 24 h ( Figure 1 B), a treatment for 48 h reduced the total cell count of the MCF7 cells with >50% in comparison to the untreated or vehicle-treated cells ( Figure 1 B), suggesting that UA inhibited the cell proliferation.…”
Section: Resultssupporting
confidence: 94%
“…To enlighten the molecular mechanisms of the cytotoxicity of UA ( Figure 1 A) on cancer cells, we first examined its ability to kill various types of cancer cells in culture by detecting plasma membrane-permeabilized cells using a membrane-impermeable propidium iodide (PI) dye. In agreement with previous reports [ 7 , 9 , 47 , 48 ], treatment with UA for 24 h induced death in human breast adenocarcinoma (MCF7) cells, osteosarcoma (U2OS) cells, cervical adenocarcinoma (HeLa) cells, and colorectal carcinoma (HCT116) cells in a dose-dependent manner, with lethal dose 50 (LD 50 ) values of 12.8 µM, 7.7 µM, 16.8 µM, and 19 µM, respectively ( Figure 1 B; Supplementary Figure S1B ). Even at a concentration of 8 μM that only killed ~5.5% of MCF7 cells in 24 h ( Figure 1 B), a treatment for 48 h reduced the total cell count of the MCF7 cells with >50% in comparison to the untreated or vehicle-treated cells ( Figure 1 B), suggesting that UA inhibited the cell proliferation.…”
Section: Resultssupporting
confidence: 94%
“…ROS is a well-known apoptosis-stimulating factor ( Pant et al, 2017 ). Current studies have demonstrated that certain anticancer active ingredients found in hawthorn, such as isoorientin ( Xu et al, 2020 ), isorhamnetin ( Li Y. et al, 2022 ), and ursolic acid ( Kang et al, 2022 ), can play a role through the ROS-mediated mitochondrial-dependent apoptosis pathway. It is mainly manifested in the induction of ROS production after drug treatment.…”
Section: Anticancer Effects and Underlying Mechanisms Of Hawthorn-der...mentioning
confidence: 99%
“…In vitro experiments confirmed that 48 h of UA treatment (16 μM) could reduce the adhesion and infiltration of the human breast cancer adriamycin-resistant cell line MCF-7/ADR to human umbilical vein endothelial cells (HUVECs) and could also reduce migration in MCF-7/ADR cells ( 68 ). UA induced cellular DNA damage and initiated G0/G1 phase arrest in embryonic cancer cells, and could be a candidate for inhibiting the recurrence of cancer ( 70 ).…”
Section: Beneficial Effects Of Uamentioning
confidence: 99%